AB0836-HPR Functional reeducation program associated with back school improve functional disability and pain in workers with chronic low back pain: a pilot study - Meira, D. M. (Annals of the rheumatic diseases, 2013)
Background Chronic Low Back Pain (CLBP) may present functional disability that compromises the performance of functional activities (1). Treatment of CLBP patients has been relying on generic exercises such as stretching and muscle strength (2). However these exercises may not cause impact the activities of daily living. Specific recruitment of deep muscles of the trunk can induce reorganization motor cortical representation in CLBP patients and may promote appropriate motor behavior (3). This is a previous study to establish the program of intervention to be used in an upcoming clinical trial. Objectives To apply an intervention of a functional reeducation program associated with back school and verify the effect on functional disability and pain in workers with chronic low back pain. Methods Twenty six (47.81±9.37 years) workers (18 female and 8 males) were included. Workers complaining of CLBP presenting current pain and limitation of movement during work activities were referred from our Occupational Health Center to participate in the study. The program consisted of 10 weeks of treatment with a 45-minute weekly session. The program was based on 3 steps applied in sequence: 1) education about spine and postural care (1 session); 2) recruitment of deep muscles of the trunk with trunk stabilizing exercises (4 sessions); 3) trunk stabilization exercises associated with movements of upper and lower limbs in different postures based on daily life activities (5 sessions). Workers also received orientation of homework assignments using illustrative self-care guidance. All workers were assessed at baseline (A1) and after 10 interventions (A2) for intensity of pain [Visual analogue scale (VAS)] and level of functional disability [Rolland–Morris Disability Questionnaire (RMDQ)]. Student-t test was used to compare the outcomes between A1 and A2. Significance level was attributed for p≤ 0.05 Results A high frequency of workers (88.85%) in the program was registered. A1 compared to A2 revealed improvement in pain (7.6±1.4 to 3.9±1.9, and functional disability (12.9±5.9 to 4.7±3.6), with p<0.001 for both. Conclusions This pilot study has proposed a functional reeducation program associated to back school; it showed that this low cost program was feasible, easy to perform at home, and attractive for workers’ adherence. Furthermore the program was effective in improving pain and functional disability in workers with CLBP. In the upcoming clinical trial, authors also intend to verify the effect in return to work. References - HOY, D; BROOKS, P; BLYTH, F; BUCHBINDER, R. The Epidemiology of low back pain. Best Practice & Research Clinical Rheumatology. 24(6). 769-781.2010 - MAGALHÃES, MO et al. Efficacy of graded activity versus supervised exercises in patients with chronic non-specific low back pain: protocol of a randomized controlled trial. BMC Musculoskelet Disord. 14(1):36. 2013 - TSAO, H; GALEA, MP; HODGES, PW. Driving plasticity in the motor cortex in recurrent low back pain. European Journal of Pain. 14. 832-839.2010 Acknowledgements We acknowledge support from Department of Physiotherapy, Communication Science & Disorders, Occupational Therapy, Faculty os Medicine, University of São Paulo, Brazil. Disclosure of Interest None Declared